The cortical deficit in humans with strabismic amblyopia - Barnes, G. R.; Hess, R. F.; Dumoulin, S. O.; Achtman, R. L.; Pike, G. B. (The Journal of physiology, 2001)
To further our understanding of the cortical deficit in strabismic amblyopia, we measured, compared and mapped functional magnetic resonance imaging (fMRI) activation between the fixing and fellow amblyopic eyes of ten strabismic amblyopes. Of specific concern was whether the function of any visual area was spared in strabismic amblyopia, as recently suggested by both positron emission tomography (PET) and fMRI studies, and whether there was a close relationship between the fMRI response and known psychophysical deficits. To answer these questions we measured the psychophysical deficit in each subject and used stimuli whose relationship to the psychophysical deficit was known. We observed that stimuli that were well within the amblyopic passband did produce reduced fMRI activation, even in visual area V1. This suggests that V1 is anomalous in amblyopia. A similar level of reduction was observed in V2. In two subjects, we found that stimuli outside the amblyopic passband produced activation in visual area V3A. We did not find a close relationship between the fMRI response reduction in amblyopia and either of the known psychophysical deficits even though the fMRI response reduction in amblyopia did covary with stimulus spatial frequency.